Effect of aqueous extract of Carica papaya dry root powder on lactation of albino rats - Tossawanchuntra G. (2014)
Effects of Carica papaya root (CP) on lactation of rats were studied using the aqueous extract from dry powder in various doses for 15, 21 and 30 days. The lactating rats were fed with distilled water and the aqueous extract of CP twice a day at doses of 400, 500 and 1,000 mg/kg/day. The level of alkaline phosphatase (ALP), prolactin and total protein in mammary gland were measured. In case of rats fed with CP for 15 days, the average weights of mammary glands of fed rats at all doses were significantly higher (p<0.05) than those of the control groups. The level of ALP in rats fed with CP at 500 mg/kg/day was highest while the level of prolactin in rats fed with CP at 400 mg/kg/day was significantly higher than other groups. Rats fed with CP at 400 and 1,000 mg/kg/day contained higher protein content than the control groups. As for rats fed with CP at 400 mg/kg/day for 21 days had higher level of ALP and the average weight of their mammary glands was significant higher than the control groups. The levels of prolactin in rats fed with CP at 400 and 500 mg/kg/day were significant higher than the control ones. The mammary glands of rat fed with CP at all doses contained higher protein content than the control groups. For rats fed with CP for 30 days, there were no significant differences in weight of mammary gland, ALP, prolactin and protein contents among the fed and control rats. It was concluded that feeding lactating rats with CP for 15 and 21 days could activate higher lactating ability by increasing the weight of mammary gland, ALP, prolactin and protein content. © ISHS 2005.